The Training on the Use of E-Cashier Application for MSMEs of Eltha Kartasura Market Snacks - Dewi Kartikasari; Maria Rosa Kumala Dewi; Leonardo Gilang Indra Nugraha; Margaretha Prihatiningsih; Evi Dewi Kusumawati; Alfa Santoso Budiwidjojo Putra (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
This Community Service activity aims to develop the knowledge and skills of Micro, Small and Medium Enterprises (MSMEs) Jajan Pasar Eltha Kartasura through e-cashier training. This service partner is one of the MSME players in Kartasura who is engaged in the culinary field. The method used in the implementation of this community service is Participatory Action Research (PAR). The implementation of these activities starts from the diagnosis stage, namely the identification of the main problems that the research subjects have and want to solve or change. The next stage is action planning identified that researchers and practitioners or other stakeholders of the research topic work together to systematically develop steps to overcome the problems that arise. The next stage is taking action with e-cashier training to increase knowledge in expediting the process of buying and selling goods aims to make it easier to record sales transactions. Furthermore, direct evaluation is carried out to find out that the solution provided can solve the problems that occur. The final stage is to identify learning by handing over 1 set of e-cashier application equipment that can assist in making sales transaction notes through the smart cashier application. After the training and mentoring, there was an increase in the knowledge and skills of MSME players in the Eltha Kartasura Market about the importance of making notes using the e-cashier application so that there is no tearing of notes. This can be seen from the comparison before and after using the e-cashier application directly. After using the E-cashier application, it can make it easier for MSME actors to make financial records. In terms of knowledge, MSME actors increase knowledge in financial management. In terms of skills, all buying and selling transactions are recorded properly, making it easier to count incoming and outgoing goods. The results obtained after the community service implementation increased turnover by 5%, which amounted to Rp3,150,000 and production capacity increased by 5% to 420 pcs.